Um breve relato sobre o Ateliê Fidalga e o Projeto Fidalga - Cinto, Sandra; Afonso, Albano (Farol, 2021)
The artists Sandra Cinto and Albano Afonso report about transformation of the study group of Ateliê Fidalga, in which they assumed the role of mediating dialogue and fostering exchanges in a horizontal process of mutual learning in art, for the Fidalga Project, composed of 4 collective workshops , three exhibition rooms, and an artistic residency program with the objective of hosting experimental exhibitions and works developed by resident artists and invited artists.